Islamic moderation in elementary school: strengthening the Aswaja Annadhliyah curriculum in preventing religious radicalism - Ibda, Hamidulloh; Wijanarko, Andrian Gandi; Azizah, Farinka Nurrahmah; Amnillah, Martin; Ro'uf, Ahmad (Journal of Education and Learning (EduLearn), 2024)
This action research aims to improve teachers’ ability to enrich, redesign, develop, and test the ahlussunah waljamaah (Aswaja) Annahdliyah curriculum in strengthening Islamic moderation in 25 madrasah ibtidaiyah (Islamic elementary schools) in Kedu Caresidenan, Central Java, Indonesia. The method used was participatory action research modeled by Stephen Kemmis, Robin McTaggart, and Rhonda Nixon, an experimental type of action research. The research findings state that Islamic moderation through strengthening the Aswaja Annahdliyah curriculum is carried out by enriching and redesigning the curriculum in the aspects of objectives, content/materials, methods/activities, and assessment/evaluation. The form of strengthening the Aswaja Annahdliyah curriculum is carried out by developing a curriculum by providing material on the basic principles of Aswaja, Ukhuwah Nahdliyah, and Mabadi Khaira Ummah in the aspects of fikrah (thought), aqidah (belief), harakah (movement), and amaliyah (worship practices). As a result, teachers know the depth and breadth of the curriculum in terms of objectives, content, methods, and evaluation at the level of fikrah, aqidah, harakah, and amaliyah, determining basic competencies, operational verbs, materials, material enrichment, and selecting appropriate learning models, methods, strategies, and media. Future research needs to explore curriculum strengthening for Aswaja Annahdliyah at the high school or university level.